The C risis in the Press. A thematic and linguistic analysis - Λέανδρος, Νίκος; Παπαδοπούλου, Δήμητρα; Ψύλλα, Μαριάννα (The Greek Review of Social Research, 2011)
This study aims to investigate how the Greek economic and social crisis was reported by the national and regional Press and the impact of ownership patterns in the perspective adopted by the media. Our corpus of research includes the two national dailies with the highest circulation in 2010 and two leading regional newspapers. The former belong to conglomerates with activities which extend beyond the media field, while the latter are published by independent publishing companies. Our method is classical thematic analysis, as well as discourse analysis, which focus on linguistic phenomena. The period of research extends from 24 April to 9 May 2010.